An esthetic approach for premature missing maxillary primary anterior teeth: A series of two case reports - Siddharth Anand; Aparna Singh; Divya Jyoti; Sulekha; Bidyut Seal (Wolters Kluwer Medknow Publications, 2021)
The aesthetic rehabilitation of a young toddler who are suffering from multiple tooth loss due to early childhood caries or extensive dental trauma is one of the challenging tasks for the Paediatric dentist in his/her day to day practise. Due to the loss of primary anterior teeth at an early age, loss of esthetic, masticatory efficiency, and mispronunciation of labiodentals sounds and development of abnormal oral habits are developed. Parent's desire plays one of the most major roles for an anterior esthetic appliance for their wards. This case report discusses and elaborates in detail one of the type of fixed anterior esthetic appliance and the considerations to be made while making treatment plan for when and why to place them.